Pendampingan Pembuatan Label Kemasan Pada UMKM Jamu Bathok Bu Tatik Di Kelurahan Wonorejo Surabaya - Syahrani Nur Aullia Octivanti; Sonja Andarini (PT. ALHAFI BERKAH INDONESIA, 2023)
UMKM Jamu Bathok Bu Tatik only carries out promotional activities by word of mouth. The sales and promotion activities are carried out in a traditional way, relying on the location of business stalls in Pasar Krukah, Surabaya. Therefore, rebranding is needed to increase the attractiveness and brand awareness. The rebranding that was carried out included creating a new logo and packaging stickers with attractive designs so that they were more eye-catching and could become the identity of the UMKM Jamu Bathok Bu Tatik which distinguished them from other herbal medicine sellers. The process required is to design and develop promotional media through the application of digital marketing which includes creating websites and business-specific emails, creating Instagram social media accounts, verifying MSME locations on Google Maps, and creating e-catalogs so that consumers can easily find out which product variants are available.